The Use Analysis of Internet Banking among SMEs Entrepreneurs - Nugraha, Indra Sungkana; Atahau, Apriani Dorkas Rambu (UNIVERSITY OF MERDEKA MALANG, 2018)
The increasing number of financial transaction activities resulted in a need of the fast, safe and efficient transaction.The increasing number of financial transaction activities resulted in people to require a payment means that was fast, safe and efficient in making transactions. Internet banking as one of the modern financial transaction means offered many conveniences in the activities. We investigated the factors that influenced the interests that had an impact on the behavior of SMEs in using internet banking. The samples of this research were 129 SMEs entrepreneurs who used internet banking in Salatiga. By using TAM modification namely Trust and Risk in Technology Acceptance Model (TRiTAM) and also actual system usage variable, we found that pertinence perception, convenience perception, attitude, and trust were factors that affected interest and affected the behavior of internet banking usage in transaction activities. The implication of this research was that the relationship among trusts, risk, and technology acceptance model with transaction behavior and internet banking could be mediated by customer interest. AbstrakJEL Classification: G41, G21DOI: https://doi.org/10.26905/jkdp.v22i3.1798